2020
DOI: 10.18775/ijied.1849-7551-7020.2015.61.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Use of E-payment Products and their Impact on Currency-in-Circulation in Nigeria

Abstract: This study is set to ascertain the relationship between the use of e-payment products and the value of currency in circulation in Nigeria. An ex-post facto research design was adopted in the investigation. A least square regression analysis was carried out on a time-series data. The objective was to ascertain relationships between the variables, whether positive or negative and to determine its significance. The outcome of the study indicates that only REMITA and WEBPAY have an inverse but significant negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The study uses POS, ATM, MBK and VCHEQ as explanatory variable while CIC is used as Dependent variable. The Ikechukwu, et (2020)…”
Section: Methodsmentioning
confidence: 99%
“…The study uses POS, ATM, MBK and VCHEQ as explanatory variable while CIC is used as Dependent variable. The Ikechukwu, et (2020)…”
Section: Methodsmentioning
confidence: 99%
“…The increase in the number of users of electronic payment channels is attributed to the novel Coronavirus pandemic in late 2019, overwhelming the health system of nations and bringing a standstill to most physical, socio-economic activities as a result of the measures put in place to curb the spread of the Virus (Akintola, Angioha & Abang, 2021;Ojong-Ejoh et al 2021;Agba et al 2021)-at this moment accelerating shift in adopting payment and purchasing preference for convenience and emphasis from health expert to avoid physical cash where possible. Electronic payment channels are becoming very popular in Nigeria since the Central Bank of Nigeria introduced the payment system vision (Oyelami et al 2020;Ikechi et al 2020).…”
Section: Introduction *mentioning
confidence: 99%
“…However, the ATM appears to be the most patronized among the e-payment channels (CBN, 2013). Thus, the progress witnessed so far has confirmed that e-payment is an integral aspect of a cashless society (Kano, Eke, Nwadiubu & Ikechukwu, 2020). In this study, we chose these 44 (Alonso et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that financial inclusion had a positive effect on economic growth. It also established that both financial inclusion and economic growth had mutual causalities Kano et al (2020). examined the influence of e-payment products on currency-incirculation in Nigeria.…”
mentioning
confidence: 99%